Electrode design and planar uniformity of anodically etched small area porous silicon - Ahmed, N. M.; Zaliman, Sauli, Prof. Madya; Uda, Hashim, Prof. Dr.; Zul Azhar, Zahid Jamal, Prof. Dr. (American Institute of Physics, 2010)
Link to publisher's homepage at http://www.aip.org/